The Effect of Using Balanced Scorecard on Competitive Advantage and Its Impact on Firm Performance - Lela Nurlaela Wati; Gunawan Triwiyono (JAAF (Journal of Applied Accounting and Finance), 2018)
English VersionThe paper is aimed to examine the effect of balanced scorecard on competitive advantage and its impact to firm performance. The samples of this research are companies that use balanced scorecard in DKI Jakarta as many as 50 companies. This research is uses primary data by giving questionnaires to corporate managers using balanced scorecard. We use Structural Equation Model with SmartPLS. The result of this research shows that there is positive effect between balanced scorecard to competitive advantage. Finding also shows that there is positive effect between balanced scorecard and competitive advantage to firm performance. The research also proves that there is positive effect between balanced scorecard to firm performance through competitive advantage. The findings of this study indicate that the better the application of balanced scorecard in the company will increase the competitive advantage and firm performance.